Hotel and Restaurant Tax Domination as a Source of Local Revenue of Badung Regency: A Study Amidst the Covid-19 Pandemic Era - Made Satria Pramanda Putra (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2020)
Pandemic Covid-19 has put significant pressure on the tourism sector and has an impact on the realisation of hotel and restaurant tax revenues in Badung Regency. This condition requires strategic steps from the Badung Regency Government to realize optimal tax revenue. The aims of this study is to examine the steps taken by the Badung Regency Government to optimise the regional tax collection from Hotel and Restaurant Taxes. This paper provides a qualitative study. Research informants are all officials in the Badung Regional Revenue Agency (Bapenda Badung Regency) as the Regional Apparatus Organization (OPD) in charge of carrying out hotel and restaurant tax levies. Data collection techniques are observation, interview and documentation study. Data collection through interview is carried out in depth and when in saturated condition will end. This study obtained results that the strategic steps taken by the Badung Regency Government in an effort to optimize the reception of Hotel and Restaurant Taxes, include (1) Utilization of Information Technology, (2) Dissemination and Education, (3) Issuance of Regulations, (4) Tax Extensification, (5) Tax Intensification, (6) Monitoring and Evaluation and (7) Legal Supremacy.